Satellite optical and radar image fusion for land cover classification - Zhang, Guobin (2018)
Nowadays, Synthetic Aperture Radar has become the most widely used radar system, since SAR images are seldom affected by weather conditions such as fog, clouds and haze. On the other hand, optical image captures more details of target object by detecting reflected solar EM radiation. However, both SAR and optical images have their own limitation. The visible details of SAR images are limited, because typical radar frequency is out of visible light frequency range. Optical images could be affected by nighttime and weather factor such as cloud and haze. Therefore, both SAR and optical images need to be combined to achieve a better land cover structure analysis result. The aim of this project was to study on image processing techniques, which will combine both SAR and optical images together to obtain a better land cover structure analysis result.